2006
DOI: 10.1194/jlr.m500510-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate: a novel stimulator of aldosterone secretion

Abstract: Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid capable of regulating critical physiological and pathological functions. Here, we report for the first time that S1P stimulates aldosterone secretion in cells of the zona glomerulosa of the adrenal gland. Regulation of aldosterone secretion is important because this hormone controls electrolyte and fluid balance and is implicated in cardiovascular homeostasis. S1P-stimulated aldosterone secretion was dependent upon the protein kinase C (PKC) isoforms a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 65 publications
2
38
0
Order By: Relevance
“…The aim of this work was to evaluate whether the stimulation of aldosterone secretion requires the intervention of signaling mechanisms other than the activation of the PLD/lipid phosphate phosphatase pathway that we described previously (1). Here, we demonstrate for the first time that activation of the PI3K/PKB and MEK/ERK pathways is essential for the stimulation of aldosterone secretion by S1P in isolated cells from the zona glomerulosa (ZG) of adrenal glands.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The aim of this work was to evaluate whether the stimulation of aldosterone secretion requires the intervention of signaling mechanisms other than the activation of the PLD/lipid phosphate phosphatase pathway that we described previously (1). Here, we demonstrate for the first time that activation of the PI3K/PKB and MEK/ERK pathways is essential for the stimulation of aldosterone secretion by S1P in isolated cells from the zona glomerulosa (ZG) of adrenal glands.…”
mentioning
confidence: 88%
“…This action involved prior activation of the phospholipase D (PLD)/lipid phosphate phosphatase pathway, Ca 21 influx from the extracellular milieu, and phosphorylation of the protein kinase C (PKC) isoforms a and y (1). S1P has been shown to stimulate the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (PKB) and mitogenactivated kinase kinase (MEK)/extracellularly regulated kinase (ERK) pathways in different cell types.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that S1P stimulates cortisol secretion in zona fasciculata bovine adrenal cells in a PKC and Ca 2+ -dependent manner (Rabano et al, 2003). In addition to stimulating cortisol secretion, S1P has been recently found to increase aldosterone production via a protein kinase C and phospholipase D-dependent pathway (Brizuela et al, 2006).…”
Section: Bioactive Sphingolipids In Steroidogenesismentioning
confidence: 98%
“…In further studies, a key role of phospholipase D (PLD) in the VLDL response was also demonstrated (Tsai et al 2014), similar to the involvement of this lipid-metabolizing enzyme in AngII-and sphingosine 1-phosphate-induced aldosterone secretion (e.g., Brizuela et al 2006, Qin et al 2010and reviewed in Bollag 2016. Thus, PLD inhibitors reduce VLDL-induced CYP11B2 expression and aldosterone secretion, as does overexpression of lipase-inactive mutants of either PLD1 or PLD2 (Tsai et al 2014).…”
Section: Vldl and Aldosterone Productionmentioning
confidence: 99%